Keeping up with the Schmidts: an empirical test of relative deprivation theory in the neighbourhood context - Gundi Knies; Simon Burgess; Carol Propper (University of Essex, Institute for Social and Economic Research (ISER), 2007)
We test empirically whether peoples life satisfaction depends on their relative income position in the neighbourhood, drawing on a unique dataset, the German Socio-economic Panel Study (SOEP) matched with micro-marketing indicators of population characteristics. Relative deprivation theory suggests that individuals are happier the better their relative income position in the neighbourhood is. To test this theory we estimate micro-economic happiness models for the years 1994 and 1999 with controls for own income and for neighbourhood income at the zip-code level (roughly 9,000 people). There exist no negative and no statistically significant associations between neighbourhood income and life satisfaction, which refutes relative deprivation theory. If anything, we find positive associations between neighbourhood income and happiness in all cross-sectional models and this is robust to a number of robustness tests, including adding in more controls for neighbourhood quality, changing the outcome variable, and interacting neighbourhood income with indicators that proxy the extent to which individuals may be assumed to interact with their neighbours. We argue that the scale at which we measure neighbourhood characteristics may be too large still to identify the comparison effect sought after.
Keywords: 330